2016
DOI: 10.1589/jpts.28.132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the thoracic flexion relaxation ratio and pressure pain threshold after overhead assembly work and below knee assembly work

Abstract: [Purpose] The purpose of this study was to compare the thoracic flexion relaxation ratio following overhead work and below-knee work. [Subjects and Methods] Ten men (20–30 years) were recruited to this study. The thoracic flexion relaxation ratio and pressure pain threshold was measured after both overhead work and below-knee work. [Results] The pressure-pain thresholds of the thoracic erector spinae muscle decreased significantly from initial, to overhead, to below-knee work. Similarly, the thoracic flexion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…According to the study by Hashemirad et al 16 ) , muscle activity pattern of the erector spinae varied with flexibility during trunk flexion/extension. The flexion-relaxation reactions are affected by several factors, including trunk loads, lumbosacral postures, trunk angular speed, number of task repetitions, and muscle fatigue 6 , 7 , 8 , 17 ) . Although previous studies were actively conducted on the effects of loads, angular speed, muscle fatigue, and postures on the flexion-relaxation rates, studies on the effects of changed lumbosacral postures of patients with chronic knee osteoarthritis on the FRP of the erector spinae have been insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Hashemirad et al 16 ) , muscle activity pattern of the erector spinae varied with flexibility during trunk flexion/extension. The flexion-relaxation reactions are affected by several factors, including trunk loads, lumbosacral postures, trunk angular speed, number of task repetitions, and muscle fatigue 6 , 7 , 8 , 17 ) . Although previous studies were actively conducted on the effects of loads, angular speed, muscle fatigue, and postures on the flexion-relaxation rates, studies on the effects of changed lumbosacral postures of patients with chronic knee osteoarthritis on the FRP of the erector spinae have been insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the feet was marked for consistency between trials. In all trials, the move from upright to full-forward flexion (forward flexion phase) was performed over 3s, followed by 3s maintenance of full flexion posture (fully flexed phase), and another 3 s to move from full-forward flexion to the upright posture (re-extension phase) 8 , 9 ) .…”
Section: Methodsmentioning
confidence: 99%
“…One study appeared to meet the inclusion criteria but was excluded because we could not con rm it was an independent sample of participants from a previously included study [19]. In total, 55 studies were included in this review, 8 of which assessed multiple measurement properties: 6 reliability (3 lumbar [20][21][22], 3 cervical [23][24][25]), 21 discriminative validity (15 lumbar [21, 22, 26-38], 6 cervical [23,24,[39][40][41][42]), 38 responsiveness (1 thoracic [43], 23 lumbar [30,36,37,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], 14 cervical [42,60,[64][65][66][67][68][69][70][71][72][73]…”
Section: Study Selectionmentioning
confidence: 99%
“…One study appeared to meet the inclusion criteria but was excluded because we could not confirm it was an independent sample of participants from a previously included study 20 . 37 studies were found to assume responsiveness but were not designed in a way to measure responsiveness (1 thoracic 21 , 23 lumbar , 14 cervical 41,[45][46][47][48][49][50][51][52][53][54][55][56][57] ). The results of these studies (characteristics, risk of bias, and data summaries) have been included in the supplementary files as they may be useful for future work in this area.…”
Section: Study Selectionmentioning
confidence: 99%